2011
DOI: 10.1080/10942910903249480
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Artisanal Honey From Tabasco, Mexico

Abstract: Potential claims for honey, floral variety and their health properties are relevant for small farmers and artisan producers. The antioxidant activity of honey samples from cacao farms, mangrove, citrus, and coconut groves from Mexico was established by applying a multiplemethod approach, which included determination of the level of total phenolic compounds and total flavonoids. Total phenolics and total flavonoids ranged from 51 to 134 mg gallic acid equivalents (GAE)/100 g honey and from 29.6 to 187.1 mg ruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…DPPH radical scavenging activity is a parameter that varied significantly (p < 0.001) depending on the botanical origin of the honey samples analyzed. By comparison to the antioxidant activities reported for honey samples from other geographical regions, which include studies by Ruiz-Navajas et al [70] who reported values of 33.4-85.5% for honey from Tabasco (Mexico) and Baltrusaityte et al [71] who reported for honey from Lithuania values between 31.1% and 86.9%, Romanian honey had overall higher antioxidant activities.…”
Section: Dpph Assaymentioning
confidence: 88%
“…DPPH radical scavenging activity is a parameter that varied significantly (p < 0.001) depending on the botanical origin of the honey samples analyzed. By comparison to the antioxidant activities reported for honey samples from other geographical regions, which include studies by Ruiz-Navajas et al [70] who reported values of 33.4-85.5% for honey from Tabasco (Mexico) and Baltrusaityte et al [71] who reported for honey from Lithuania values between 31.1% and 86.9%, Romanian honey had overall higher antioxidant activities.…”
Section: Dpph Assaymentioning
confidence: 88%
“…These bioactive compounds are able to act as reducing agents, free radical scavengers, metal chelators or deactivators of singlet oxygen and/or display simultaneously more than one of these functions (Gramza et al, 2004). Its antioxidant properties also interfere with oxidative reactions of chain propagation (Ruiz-Navajas et al, 2011). Table 1 shows the concentrations of flavonoids and phenolic compounds found in the ethanol extracts.…”
Section: Total Contents Of Phenol and Flavonoidsmentioning
confidence: 99%
“…However, some samples of fresh honey have similar levels of antioxidant capacity to the values found in this work. For example, it has been reported values between 33.4 and 85.5% for honeys from Tabasco (México) [16] and in honeys from Lithuania values between 31.1 and 86.9% in DPPH reaction system [35].…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 99%
“…Honey from Mexico enjoys the preference of consumers around of the world due to its good sensory and nutritional properties. Several studies have reported the physicochemical properties and the antioxidant capacity of different types of artisanal or fresh honeys from México [13][14][15][16]. In the Mexican market it is also possible to purchase different honey brands, which normally are subject to an industrial packaging process that includes heating and filtering.…”
Section: Introductionmentioning
confidence: 99%